The Impact of Service Quality, Patient Satisfaction, and Trust on Positive Word of Mouth (WOM) of Dental Clinic’s Patients - Hans Kristian Wibowo; Sheellyana Junaedi (AIBPM Publisher, 2019)
The purpose of this research is to study the impact of service quality, patient satisfaction, and trust on positive word of mouth (WOM) recommendations by dental clinic patients. The paper also investigates the mediating effect of loyalty on WOM. A survey involving 150 dental clinic patients is conducted using a structured questionnaire developed using existing constructs. Data are analyzed using regression analysis with mediation which is used to assess the degree of association between the constructs and also applied to analyze the mediating effect of loyalty. The study is limited to a small sample which may somewhat limit generalization of findings. The results show that service quality has neither direct nor indirect significant relathionship towards positive WOM, patient satisfaction has indirect significant relationship through the medium of loyalty towards positive WOM, and trust has both direct and indirect significant relationship through the medium of loyalty towards positive WOM of dental clinic’s patients. This study makes several contributions. For academic, this study establishes the importance of service quality, patient’s satisfaction, and trust as antecedents of WOM in the context of dental clinic patients and also establishes loyalty as the mediating factor between them. For practical, the result provides insights about factors that can influence positive WOM of dental clinic patients. Also, it is beneficial for dental clinic management to consider the promotion strategy.